Analisis Kepuasan Pelanggan Terhadap Bauran Pemasaran Menggunakan Integrasi Importance Performance Analysis dan Model Kano (Studi Kasus : Lâsociete Dine and Bar Bandung) - Wahyuniardi, Rizki; Syaifulbachri, Asep; Algaza, Rasyid (Universitas Katolik Parahyangan, 2018)
The city of Bandung has a variety of culinary places that feature their own characteristics, ranging from luxury culinary venues, traditional uniqueness hangout, to the roadside hangout is available in this city. Amid the rapid development of culinary tourism in the city of Bandung, Lsociete Dine and Bar is one restaurant that wrestle in culinary tourism business competition. However, according to sales data, Lsociete experienced a decrease in total sales from 2014 to 2016. Lsociete requires effective improvement on its marketing mix performance. The study aims to analyze customer satisfaction with Lsociete marketing mix. The research was conducted using descriptive statistics method, measuring customer satisfaction index and integration of Importance Performance Analysis and Kano Model.Based on the result of research, there are some attributes of Lsociete marketing mix that need to be improved. For price attributes, Lsociete should review product prices. This review is conducted through further research on product pricing by analyzing product prices with competitor product price comparison or optimizing production costs. For promotional attributes, Lsociete can hold live music on an ongoing basis. In addition to this, it can be proposed packages with attractive discounts to the customer, group or family. This is important to consider because Lsociete puts forward a convenient facility to its customers to feel different from its competitors.Â Keywords: marketing mix, importance performance analysis, integration of importance performance analysis and canoe model, customer satisfaction, Kano model